Corporate Security: Identifying and Understanding the Levels of Security Work in an Organisation - Ludbey, Codee Roy (Asian journal of criminology, 2018)
The study undertook an examination of corporate security through the lens of the broader socio-organisational literature to understand its organisational stratum, seating, and function. The methodology applied a survey questionnaire to security practitioners, incorporating two measurement tools to assess work level and time-span of discretion. Findings identified work levels across the corporate security function. These work levels indicate that the corporate security function operates at the operational and tactical strata, with limited strategic executive impact. Furthermore, the corporate security function is positioned within the technostructure, providing analytical support to business operations. The study identified a significant disconnect between the corporate security literature—as written by security practitioners and academia—and the socio-organisational literature, with many points of divergence. These findings suggest the need for study replication and a review of the security literature in regards to executive influence.